Apparent damping induced by spurious pitching in shaking table testing. - Molina, F.J (Earthquake engineering & structural dynamics.)
A seismic shaking table test performed on a one storey steel frame with an 8 ton RC floor slab was reproduced on a similar specimen by means of the pseudo dynamic (PsD) method. A satisfactory agreement of the results could only be achieved after recalibration of the theoretical mass in the PsD equation and proper inclusion in the PsD test input of the horizontal and pitching accelerations measured on the table. In the shaking table test, the spurious pitching lotion produced a significant increase in the apparent damping that could be estimated as a function of the pitching dynamic flexibility of the system. Dynamic and PsD snap back tests were also performed to provide an additional check of the reliability of the PsD method. The spurious pitching motion of the shaking table should always be measured during the tests and reported as a mean to increase the reliability and usefulness of the results.